Employer branding : measuring undergraduates' intentions to apply to an organization. - Wang, Wan Ting. (2009)
Facing the downturn in economy today, it is more important than ever before for organizations to attract talents. The aim of our study is to present a list of essential factors that will influence graduates today in their intention to apply for an organization. Through our analysis of the factors involved, we will provide recommendations to tackle the issues on employer branding that are faced by organization today in their never-ending quest to attract talents.